Necesidad de implementar en el código orgánico de la niñez y adolescencia el sustento y alimentación compartida por los progenitores - Torres Jiménez, Beatriz Consuelo (2016)
The Constitution of the Republic is established clearly the right to food which all Ecuadorians have, and access to them from safely and permanently, makes mention that these are safe and nutritious, this track that the inhabitants of this country, have a good live and surrounded by what is necessary, including that of the right to food. Parenting is not only to procreate children, but especially to educate them, love them, try them all necessary means so that they grow, mature, and live in a suitable and proper environment for development as people. Educate happy children requires parents a "knowledge be" and a "poise" for this wonderful task, having clear a goal and a concrete plan of "joint action" to teach them values, teach virtues and correct them as needed. Speaking of food in family law is to refer to the essential means to meet all the basic needs of the family, in accordance with their specific socio-economic position. It includes not only food but also education, housing, transportation, dress, medical care, recreation, etc. The obligation to ensure these foods usually rests with parents toward children, but in practice the burden of food leave it only to the a parent who does not have parental authority, hence, their rights are violated. The code of children and adolescents must be reformed by implementing the obligation of support and power shared by the parents, i.e. the person who has custody of the minor is in the same form justify and contribute monthly contribution for food, livelihood and welfare of the minor, provided it works and has the financial means sufficient , for this must be in the same form as the parent does or alimony.